TADARUS AL-QUR’AN DI MASJID BAITURROHMAH MAMBIL SEBAGAI PENGUATAN KECERDASAN SPIRITUAL ANAK - Dewi Mawardini, Intan; Iflahathul Chasanah; Azka Putri, Anninda (Islamic Elementary School (IES), 2024)
During childhood, it is very necessary to pay serious attention to all aspects of their development, including the development and strengthening of their spiritual intelligence. This modern and sophisticated era is known as an era full of life challenges and competition. Through the Koran, children can hone and develop the potential of their spiritual intelligence. By reading the Qur'an, children can actualize spiritual intelligence. The type of research used in this research is descriptive qualitative research. The tadarus al-Qur'an activity organized by the takmir of the Baiturrohmah Mosque provides strengthening of spiritual intelligence in good children, including being more active and happier, interacting well with other people, making relationships with others faster and closer